The Impact Of Voter Initiatives On Economic Activity - S. Brock Blomberg; Gregory D. Hess; Akila Weerapana (Wellesley College, Department of Economics, 2001)
Recent studies have claimed that states with initiatives systems of legislation use this more direct from of democracy to improve productive resource allocation. This paper compares the economic performance of states with initiatives to states that do not have initiatives. We first construct a simple growth model to identify the channel through which initiatives play an important role in determining economic activity; we then test the implications of this model using data for the 48 contiguous United States over the years 1969-1986. Our findings suggest that states with initiative systems waste between 20 to 30 percent fewer resources than do non-initiative states resulting in better economic performance in terms of higher GDP growth and faster convergence.
Keywords: H1; H8; H5; 330; Growth; Initiatives; Voting; Bürgerinitiative; Ökonomische Theorie der Demokratie; Wahlverhalten; Wirtschaftswachstum; USA